The Canadian Neuromuscular Disease Registry: Connecting patients to national and international research opportunities. Issue 1 (8th December 2017) - Wei, Yi; McCormick, Anna; MacKenzie, Alex; O'Ferrall, Erin; Venance, Shannon; Mah, Jean K; Selby, Kathryn; McMillan, Hugh J; Smith, Garth; Oskoui, Maryam; Hogan, Gillian; McAdam, Laura; et al.
Abstract: Introduction: Patient registries serve an important role in rare disease research, particularly for the recruitment and planning of clinical trials. The Canadian Neuromuscular Disease Registry was established with the primary objective of improving the future for neuromuscular (NM) patients through the enablement and support of research into potential treatments. Methods: In this report, we discuss design and utilization of the Canadian Neuromuscular Disease Registry with special reference to the paediatric cohort currently enrolled in the registry. Results: As of July 25, 2017, there are 658 paediatric participants enrolled in the registry, 249 are dystrophinopathies (229 are Duchenne muscular dystrophy), 57 are myotonic dystrophy participants, 98 spinal muscular atrophy participants and 65 are limb girdle muscular dystrophy. A total of 175 patients have another NM diagnosis. The registry has facilitated 20 clinical trial inquiries, 5 mail-out survey studies and 5 other studies in the paediatric population. Discussion: The strengths of the registry are discussed. The registry has proven to be an invaluable tool to NM disease research and has increased Canada's visibility as a competitive location for the conduct of clinical trials for NM therapies.